Followership in health care clinicians: a scoping review protocol. Issue 12 (11th December 2021) - Alanazi, Sulaiman; Wiechula, Richard; Foley, David
ABSTRACT: Objective: The main objective of this scoping review is to identify and map followership literature in order to understand the current state of followership research in relation to health care clinicians. Introduction: Health care clinicians need to be flexible in switching between leader and follower roles as appropriate to advance patient care; however, much of the research effort in this regard has primarily concentrated on leadership. Effective followership in health care organizations may be necessary to enhance clinical team performance in order to improve patient safety and quality of care. There have been increasing calls in the literature recommending research of followership in the provision of health care. Thus, it is important to synthesize the available evidence on followership to identify what has been studied and highlight research gaps in this area. Inclusion criteria: The review will focus on followership in health care clinicians. Only studies with participants who are health care clinicians will be included. The review will include studies of quantitative, qualitative, and mixed methods designs; systematic reviews; and meta-analyses. Methods: The search will include JBI Evidence Synthesis, Cochrane Database of Systematic Reviews, CINAHL, MEDLINE, EPPI-Centre, Scopus, and Epistemonikos. In addition, unpublished or gray literature will be searched in ProQuest Dissertations and Theses Global and Google Scholar. No limits on date or language will be applied to the search. Data will then be extracted from included papers by three independent reviewers. Results from extracted data will be presented in tabular form accompanied by a narrative summary.